ANALYSIS OF OSCILLATING ROD OF HORIZONTAL LOGARITHM PERIOD ANTENNA UNDER WRAP ICE - SONG ZongFeng; WANG ZuoXiang; GUO Wei (Jixie qiangdu)
Analysis of oscillating rod of rigid structure horizontal log-periodic antenna under wrap ice was performed,due to winter weather oscillating rod is bent,somewhere in the north in February 2014.In the finite element software ANSYS platform,to wrap the ice thickness,wrap ice when wind speed is known conditions,a detailed analysis of wrapped ice of bending oscillating rod was performed.The results show that the actual thickness beyond the design wrapped ice thickness.So cause the wrap ice load and wind load area increases,beyond the oscillating rod and its cable carrying capacity,resulting in instability of the oscillating rod bent.According to the oscillating rod bent reason,in order to meet the requirements of heavy ice wrapped,the improved design of the oscillating rod was proposed.